UMP researcher finds different clade in Covid-19 genome sequencing result - UMP, PNC (2020)
Kuantan, 9 June 2020 – A researcher from Universiti Malaysia Pahang (UMP) who carried out a genome sequencing study, “Whole Genome Sequencing of Circulating Covid-19 Strains in Malaysia”, discovered a different lineage of the clade of Covid-19.